Analysis of Power Losses Due to Load Imbalance and Loss Calculation in Distribution Transformers: Merauke City Customer Service Unit - Nicholas Johansyah; Tri Wahyu Adi; Herry Nugraha (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2025)
This study analyzes power losses due to load imbalance and the calculation of losses in distribution transformers at the Merauke City Customer Service Unit (ULP). The results show that most distribution transformers on the Angkasa, Bampel, Parako, Kompi, and Ermasu feeders experienced load imbalances exceeding the 20% tolerance limit according to SPLN D3.002-1:2014 standards, contributing to increased neutral currents and power losses, particularly in transformers with heavy loads and uneven phase distribution. After phase current balancing using ETAB 19, significant reductions in neutral current and losses were observed, with transformer efficiency increasing by an average of 2-5% per unit. A feeder-based, data-driven balancing strategy, involving the redistribution of load from dominant phases to deficit phases along with regular monitoring, proved effective in improving distribution system efficiency, extending transformer lifespan, and enhancing voltage quality for customers. These findings provide an operational basis for PLN ULP Merauke to prioritize distribution network improvements, maintain a minimum bus voltage profile of 93–95%, and reduce operational costs through regular load balancing.